Extremal problems in a class of mappings with bounded integral characteristics - Gol'berg, A. L. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We consider mappings with bounded integral characteristics. We construct extremal mappings of plane rings realizing the minimum of these characteristics.